A Systematic Literature Review of Gamification for Children: Game Elements, Purposes, and Technologies - Nia Semartiana; Atina Putri; Yusep Rosmansyah (Universitas Respati Yogyakarta, 2022)
Technology continues to develop tools and applications to help students learning, especially in early childhood education. This innovation has an impact on children's learning behavior and activities since children are familiar with and enjoy playing with digital games. Previous research has attempted to combine the fun aspects of games with the learning aspects of games to create child-friendly activities. Gamification helps to create an effective educational environment in order to increase children's motivation, engagement, and learning performance. However, there are few studies that discuss the impact of gamification on children's learning, as well as the types of game elements and technology that are acceptable for them. This study presents a systematic literature review on gamification in order to identify the types of goals, game elements, and trends in gamification technology for the younger generation. In this study, 20 research articles were selected to be reviewed from four database sources (IEEE Xplore, ScienceDirect, Scopus and ACM) from 2017 to 2021. The results showed that the primary goal of gamification for children were to increase motivation and engagement. Several elements, such as points, levels, and leaderboards, were frequently used in the game. Finally, mobile applications were commonly used for gamification in the learning process of children.